IMPLEMENTATION OF THE 2024 GENERAL ELECTION IN NANGGROE ACEH DARUSSALAM PROVINCE REVIEW OF PROCEDURAL DEMOCRACY - M. Nur Akhyar; Samugyo Ibnu Redjo; Dede Sri Kartini; Ismail Nurdin; Hawary Annisa (Jurnal Ilmiah Wahana Bhakti Praja, 2025)
The 2024 elections in Aceh reflect unique dynamics in the context of procedural democracy and special autonomy. The characteristics of elections in Aceh are influenced by the recognition of local political parties regulated through Law Number 11 of 2006 concerning the Government of Aceh, as a result of the 2005 Helsinki MoU. Local parties such as the Aceh Party (PA) and the Nanggroe Aceh Party (PNA) compete with national parties in reflecting the aspirations of the Acehnese people. This study uses a qualitative approach with document studies to analyze the implementation of elections in Aceh, including voter participation, local political dynamics, and the effectiveness of election administration. The results showed an increase in voter participation compared to the previous election, with the highest participation recorded in the presidential election (87.01%). However, challenges such as money politics, campaign abuses, and security stability remain significant issues. In addition, the role of the young generation and women in elections has begun to be strengthened through political party strategies. In the context of procedural democracy, these elections reflect efforts to meet Robert Dahl's criteria, including equal voting, effective participation, and agenda oversight. In conclusion, the 2024 election in Aceh is not only a democratic mechanism but also an instrument to strengthen peace and special autonomy. These findings provide insight into the challenges and opportunities of local democracy in Aceh.